Abordagem estratégica orientada para o gerenciamento integrado de operações: o caso da produção de petróleo do pré-sal da bacia de Santos - Lima, Claudio Benevenuto de Campos (2013)
Over the last decade, the oil industry has aimed to improve the efficiency of work processes by redesigning them, in order to provide data and information in the required time, with the proper systems and engineering tools demanded to faster and better decisions. This strategy has been adopted by many oil operators and service companies. Currently, Integrated Operations is being deployed in Santos Basin (Brazil) with important impacts on the production of pre-salt. In this sense, the objective of this research is to evaluate, in the described context, the implementation of Integrated Operations on a particular oil company. As a methodological option, through a literature review, the main initiatives of the oil industry were analyzed as well as application cases. As an instrument of intervention, it was used an approach proposed by a consortium of international organizations - the IO Center, coordinated by NTNU (Norwegian University of Science and Technology), which allows to understand the value creation in Integrated Operations projects. In cooperation with NTNU, the suggested framework was adjusted for use in Santos Basin, allowing the study of the potential gains, case analysis and diagnosis of gaps in implementation of Integrated Operations. Additionally, an online survey was performed involving the workforce to understand new opportunities for implementation of Integrated Operations and change management. As a result of the application, it was possible to identify improvement actions and benefits pointing to a great attractiveness of this approach